2021
DOI: 10.2113/2021/8465197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polar Molecule Aggregation on the Stability of Crude Oil/Water Interface: A Molecular Simulation Study

Abstract: To ensure the efficient operation of crude oil dehydration and sewage treatment technology in oilfield surface production system, the effect mechanism of polar components represented by asphaltene and resin on the formation and stability of oil-water emulsion needs to be revealed at nanoscale. In this paper, the molecular dynamics simulation method was used to construct the crude oil/polar component/water system models with different molar ratios of asphaltene to resin by adjusting the number of asphaltene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…At present, extensive research has shown that the oil-water interfacial films formed by the asphaltenes in heavy oil at the heavy oil-water interface play a major role in the stabilizing of heavy oil-water emulsions [117][118][119][120][121]. In addition, the other surface-active components (resins, naphthenic acid and amphiphilic solid particles) have an important influence on the interfacial characteristics of asphaltene interfacial films [122][123][124][125].…”
Section: Interface Characteristics Of Asphaltene Interfacial Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, extensive research has shown that the oil-water interfacial films formed by the asphaltenes in heavy oil at the heavy oil-water interface play a major role in the stabilizing of heavy oil-water emulsions [117][118][119][120][121]. In addition, the other surface-active components (resins, naphthenic acid and amphiphilic solid particles) have an important influence on the interfacial characteristics of asphaltene interfacial films [122][123][124][125].…”
Section: Interface Characteristics Of Asphaltene Interfacial Filmsmentioning
confidence: 99%
“…At present, extensive research has shown that the oil-water interfacial films formed by the asphaltenes in heavy oil at the heavy oil-water interface play a major role in the stabilizing of heavy oil-water emulsions [117][118][119][120][121]. In addition, the other surface-active components (resins, naphthenic acid and amphiphilic solid particles) have an important influence on the interfacial characteristics of asphaltene interfacial films [122][123][124][125]. Therefore, based on the understanding of the structural characteristics of natural surface-active components in Section 2.2.1, the interface characteristics of asphaltene interfacial films are reviewed and discussed in detail in this section.…”
Section: Interface Characteristics Of Asphaltene Interfacial Filmsmentioning
confidence: 99%